2003
DOI: 10.1037/0012-1649.39.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories leading to school-age conduct problems.

Abstract: The present study applied a semiparametric mixture model to a sample of 284 low-income boys to model developmental trajectories of overt conduct problems from ages 2 to 8. As in research on older children, 4 developmental trajectories were identified: a persistent problem trajectory, a high-level desister trajectory, a moderate-level desister trajectory, and a persistent low trajectory. Follow-up analyses indicated that initially high and low groups were differentiated in early childhood by high child fearless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
576
3
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 520 publications
(623 citation statements)
references
References 64 publications
35
576
3
9
Order By: Relevance
“…This is in contrast to the deteriorating slope of involvement for mothers in the control group, for whom destructive behavior showed only modest decreases between ages 2 and 3. This result is consistent with a primary goal of the intervention-to sustain parental engagement at age 2 when patterns of family coercion are likely to emerge and lead to more serious CP (Shaw et al, 2003).…”
Section: Promoting Maternal Involvementsupporting
confidence: 84%
See 2 more Smart Citations
“…This is in contrast to the deteriorating slope of involvement for mothers in the control group, for whom destructive behavior showed only modest decreases between ages 2 and 3. This result is consistent with a primary goal of the intervention-to sustain parental engagement at age 2 when patterns of family coercion are likely to emerge and lead to more serious CP (Shaw et al, 2003).…”
Section: Promoting Maternal Involvementsupporting
confidence: 84%
“…As a result, parental pleasure in child rearing has been shown to decrease from the 1st to 2nd years (Fagot & Kavanagh, 1993). How caregivers respond to these changes and how involved they are during this period have been shown to have important repercussions for early CP (Gardner et al, 1999;Shaw et al, 2000Shaw et al, , 2003, as the course of CP has been shown to be moderated by controlling, uninvolved, and rejecting parenting (Aguilar et al, 2000;Campbell et al, 1996). Preventive interventions that can demonstrate changes in parental involvement, responsiveness, or rejecting behavior have the potential to modify trajectories of child CP.…”
Section: The Toddler Years As a Period Of Transition For Children Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen percent of the children exhibited moderate levels of PA while 3% exhibited high levels. Second, Shaw, Gilliom, Ingoldsby, and Nagin (2003) distinguished among four groups of boys with distinct levels of conduct problems between the ages of 2 and 8 years among their sample of low income boys (n = 284). Six percent of those boys already exhibited elevated levels in toddlerhood and maintained high levels in middle childhood (Shaw et al, 2003).…”
Section: Atypical Developmental Patternsmentioning
confidence: 99%
“…Second, Shaw, Gilliom, Ingoldsby, and Nagin (2003) distinguished among four groups of boys with distinct levels of conduct problems between the ages of 2 and 8 years among their sample of low income boys (n = 284). Six percent of those boys already exhibited elevated levels in toddlerhood and maintained high levels in middle childhood (Shaw et al, 2003). Thus, some preschoolers may already present levels of aggression that represent a risk for future problems, and the elevated levels of aggression observed in school age children might be the continuation of a pattern that started in toddlerhood.…”
Section: Atypical Developmental Patternsmentioning
confidence: 99%